Experience of extended transtriceps approach in osteosynthesis of complex fractures of the distal metaepiphysis of the humerus - A. Yu. Sergyeev; A. M. Fain; A. Yu. Vasa; S. F. Gnetetsky; V. B. Bondarev (Неотложная медицинская помощь)
Background. The preferred treatment for intra-articular displaced fractures is open reduction and internal fixation. The need to obtain a better visualization of the fracture geometry made it necessary to develop a large number of new approaches and their modifications.Material and methods. The study included 186 patients with an intra-articular fracture of the distal humerus, who underwent plate osteosynthesis using the standard technique. The main group included 112 patients who were operated on using ETTA. The comparison group included 74 patients with a similar type of fracture, who were operated on using chevron olecranon osteotomy. The groups were comparable in terms of age, gender, mechanism of injury, and nature of the fracture. Long-term results were evaluated in 186 patients (minimum follow-up period – 12 months).Results. Comparative analysis revealed that the time of surgery was reduced by an average of 20 minutes (p=0.03) in the main group. The immediate and medium-term results were assessed according to the data of physical examinations, control radiography, dynamics of the increase in the amplitude of motion in the elbow joint. The results were comparable. When assessing complications, the migration of fixators was detected in 5.5% in the main group and 16% in the comparison group. In the comparison group, failure of union of the olecranon after osteotomy, migration of wires with skin perforation, and reactive bursitis were observed.Conclusion. 1. The extended transtriceps approach provides good visualization for fixing fractures of the distal humerus. 2. Evaluation of treatment results confirms that osteosynthesis using this access allows to reduce the time and trauma of the operation, to avoid complications associated with osteotomy of the olecranon, and to carry out successful postoperative rehabilitation, achieving good functional results.